2013
DOI: 10.1021/jp409111m
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Study of a Metastable-State Photoacid

Abstract: A photoacid that possesses a metastable acidic state induced by visible light is studied. Previous work showed that this photoacid can reversibly produce a large pH change capable of controlling chemical reactions, altering material properties, and killing bacteria. In this work, we studied the relaxation kinetics of the metastable acidic state in different solvents including water, ethanol, and DMSO. In all of these solvents, the kinetic data can be fitted well to a second-order rate equation, which indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 22 publications
4
66
0
1
Order By: Relevance
“…Absorption at 436 nm recovered to nearly the original level in 30 min. The data of the early stage of the reaction can be fitted to a second‐order kinetic equation . The rate constant was calculated to be 74 M −1 s −1 , which is close to that of mPAH 1 (73 M −1 s −1 ).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Absorption at 436 nm recovered to nearly the original level in 30 min. The data of the early stage of the reaction can be fitted to a second‐order kinetic equation . The rate constant was calculated to be 74 M −1 s −1 , which is close to that of mPAH 1 (73 M −1 s −1 ).…”
Section: Resultsmentioning
confidence: 67%
“…In fact, radical polymerization of spiropyran monomers has been reported before . In addition, our prior work showed that the spiropyran form of the photoacid relaxed back to the merocyanine form at a very low rate in DMSO . Therefore, we hypothesized that if the polymerization was in DMSO under a basic condition, the photoacid would stay in the spiropyran state and would not quench the radical polymerization.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[10] In particular, PAGs offer remote spatial and temporal control because of their capability for irradiationinduced proton dissociation. [12] This unique physicochemical property perfectly meets the demands described above. [11] Theliberated protons may have al ong enough lifetime to diffuse away from their counterions and cause ac hemical process.F or instance, protonated merocyanine (MEH), which is based on aphotochromic reaction in which the proton dissociation state is stabilized by an intramolecular photoreaction, has been reported as al ong-lived photoacid.…”
mentioning
confidence: 56%
“…When the solution was irradiated with white light, in addition to the rapid color change from yellow to white (Figure 2Cinset), the pH decreased to 3.9 within 20 s( Figure 2C), indicating that MEH is ap hotoinduced strong acid based on an intramolecular photochromic reaction. [12] Additionally,w ep erformed an additional four on/off light cycles (Supporting Information, Figure S2). This result indicates that the long-lived MEH is stable when in the proton dissociation state,i ndicating it is an effective proton source for driving ATPase rotation to synthesize ATP.…”
mentioning
confidence: 99%